2-3m=5-m

Simple and best practice solution for 2-3m=5-m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-3m=5-m equation:


Simplifying
2 + -3m = 5 + -1m

Solving
2 + -3m = 5 + -1m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add 'm' to each side of the equation.
2 + -3m + m = 5 + -1m + m

Combine like terms: -3m + m = -2m
2 + -2m = 5 + -1m + m

Combine like terms: -1m + m = 0
2 + -2m = 5 + 0
2 + -2m = 5

Add '-2' to each side of the equation.
2 + -2 + -2m = 5 + -2

Combine like terms: 2 + -2 = 0
0 + -2m = 5 + -2
-2m = 5 + -2

Combine like terms: 5 + -2 = 3
-2m = 3

Divide each side by '-2'.
m = -1.5

Simplifying
m = -1.5

See similar equations:

| X+2y=336 | | P+3=13+7 | | 25x=3500 | | 7x^3+12x+17=0 | | 7(k-4)=-98 | | 4x-4.6/5=6.2 | | -7(w-4)+3w-27=p | | 7x+8=8x+56 | | 2x-8x=-20 | | 32=2/5(15p-10)p= | | 5(F-32)=-558.9 | | -6/7=1/2y-2/5 | | 5-(x/8)=10 | | X+5=12+2 | | 224=3(n-5) | | 3x+15=6x+21 | | 4n=9n-23 | | X=(y-6)/4 | | a-9=25 | | 7(1-x)=10-6(x+2) | | 4x-12=-4(7x+3)-7x | | 2.3x+1.2+2.5x=19.4-4.3x | | 1-4(u-1)=p | | 8x+12=12+8x | | 2(x+y)+y-6+10y= | | S-6=3-3 | | (4n-3)+(2n+5)= | | 0=x^5-6x^3+x | | 4(-4)-3y=-10 | | 6-6Z=-2(X+5) | | (79x-61y)(49x+5y)= | | 7a/10-3a/10 |

Equations solver categories